Serum cytokine levels in patients with acute brucellosis and their relation to the traditional inflammatory markers - Demirdag, K; Ozden, M; Kalkan, A; Godekmerdan, A; Kilic, SS (Wiley, 2003)
The number of clinical studies on gamma interferon (IFN-gamma), tumor necrosis factor-alpha (TNF-alpha) and interleukin-4 (IL-4) in human brucellosis is limited. The present study was focused on IFN-gamma, TNF-alpha and IL-4 levels in acute brucellosis cases, in the acute phase and at the end of the treatment. The relation of these cytokines to traditional inflammation markers was also investigated. The study included 27 cases of acute brucellosis and 20 healthy volunteers who had no complaints. It was found that mean IFN-gamma and TNF-alpha levels, CRP (C-reactive protein) levels and ESR (erythrocyte sedimentation rate) values were significantly higher in acute brucellosis cases as compared to post-treatment values and values measured in the control group. In addition, IFN-gamma and TNF-alpha levels measured in the acute phase correlated with the increase in CRP levels and ESR values. Our results confirmed that IFN-gamma and TNF-alpha are involved in the pathophysiology of brucellosis and are closely related to the inflammatory activation of the disease. In view of the present findings, it is suggested that IFN-gamma and TNFalpha may be used for monitoring brucellosis. (C) 2003 Federation of European Microbiological Societies. Published by Elsevier B.V.. All rights reserved.
Keywords: brucellosis; cytokine; inflammatory marker; treatment